2017
DOI: 10.1111/anu.12632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ingredient particle sizes and dietary viscosity on digestion and faecal waste of striped catfish (Pangasianodon hypophthalmus )

Abstract: The ingredients' particle size and dietary viscosity may alter digestion, performance and faecal waste management of fish. This study aimed to assess the effect of grinding screen sizes of feed ingredients and dietary viscosity on digestibility, faecal waste and performance of striped catfish (Pangasianodon hypophthalmus, Sauvage, 1878). The experiment had a 2 × 3 factorial-design: two feed mesh particle sizes, by grinding ingredient mixtures at two screen sizes (0.8 versus 1.0 mm); and three dietary viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
3
16
2
Order By: Relevance
“…Therefore, amberjack did not return to full appetite. This phenomenon probably occurs even in the case of feeding diet with small amount (0.5%) of GG supplementation combined with 2.5% AG because of GG being more viscous than AG and CMC (Tran-Tu, Hien, Bosma, Heinsbroek, and Verreth (2018)). Based on the present results of FI and GET in the amberjacks, feeding diet with more viscous binder too frequently and/or at shorter period can result in poorer FI because of prolonged GET in amberjack juvenile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, amberjack did not return to full appetite. This phenomenon probably occurs even in the case of feeding diet with small amount (0.5%) of GG supplementation combined with 2.5% AG because of GG being more viscous than AG and CMC (Tran-Tu, Hien, Bosma, Heinsbroek, and Verreth (2018)). Based on the present results of FI and GET in the amberjacks, feeding diet with more viscous binder too frequently and/or at shorter period can result in poorer FI because of prolonged GET in amberjack juvenile.…”
Section: Discussionmentioning
confidence: 99%
“…In monogastric animals such as pig, broiler, and fish, diets with higher viscosity result in slower elimination of digesta from the stomach (Rainbird & Low, 1986; Refstie, Svihus, Shearer, & Storebakken, 1999). Tran‐Tu, Hien, Bosma, Heinsbroek, and Verreth (2018) showed that increased dietary viscosity has negative effects on growth and digestibility in striped catfish, Pangasianodon hypophthalmus . When comparing the viscosity of the present test diets, it was the highest in the CMC and the lowest in the AG diets.…”
Section: Discussionmentioning
confidence: 99%
“…Feeds were formulated in order to meet the nutritional demands of the species in this stage of development (Table 1), according to the Brazilian tables of tilapia nutrition (FURUYA, 2010). Each nutrient in the feed was expressed with the aid of the program SuperCracr 6.1 Master (TD, 2019).…”
Section: Materials E Methodsmentioning
confidence: 99%
“…Depending on the strategy used for feed processing, fish may face difficulties during feeding, leading to significant nutrient losses, and consequently, affecting the tanks water quality negatively (RODRIGUES, FERNANDES, 2006;BITTENCOURT et al, 2012). The identification of the ideal pellet size is one of the most important aspects regarding fish nutrition (TRAN-TU et al, 2017), especially during larviculture and nursery stages, given the small size of fish (BAILEY et al, 2003), and consequently its mouth opening.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing the CHO:LIP ratio by increasing lipid content resulted in decreased moisture and crude protein (CP) contents whereas fat and ash contents increased (Ali & Al‐Asgah, ; Haidar, Bleeker, Heinsbroek, & Schrama, ). Changing the CHO:LIP ratio can also have an impact on the apparent digestibility coefficient (ADC) of the nutrients, energy efficiency and waste composition (Amirkolaie, Verreth, & Schrama, ; Tran‐Tu et al, ). Two factors (i.e.…”
Section: Introductionmentioning
confidence: 99%